2011
DOI: 10.1089/ars.2010.3738
|View full text |Cite
|
Sign up to set email alerts
|

Role of Reactive Oxygen Species-Related Enzymes in Neuropeptide Y and Proopiomelanocortin-Mediated Appetite Control: A Study Using Atypical Protein Kinase C Knockdown

Abstract: These results may further the understanding of ROS-RE and aPKC in the control of PPA anorexia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 57 publications
1
31
0
Order By: Relevance
“…Moreover, as the activation of hypothalamic POMC contributes to the protection of brain against oxidative stress, as described in our previous reports (Hsieh et al, 2011;Kuo et al, 2011) and STAT3 is sensitive to redox stress and is a logical candidate for redox modification by oxidants and antioxidants (Zgheib et al, 2012), compounds that could activate POMC and PI3K/STAT3 signalling might be applied, as therapeutic agents, to the improvement of oxidative damage induced by amphetamine.…”
Section: Figurementioning
confidence: 69%
See 1 more Smart Citation
“…Moreover, as the activation of hypothalamic POMC contributes to the protection of brain against oxidative stress, as described in our previous reports (Hsieh et al, 2011;Kuo et al, 2011) and STAT3 is sensitive to redox stress and is a logical candidate for redox modification by oxidants and antioxidants (Zgheib et al, 2012), compounds that could activate POMC and PI3K/STAT3 signalling might be applied, as therapeutic agents, to the improvement of oxidative damage induced by amphetamine.…”
Section: Figurementioning
confidence: 69%
“…These neurons may influence the function of neuropeptide Y (NPY) and pro-opiomelanocortin (POMC) neurons involved in ingestive behaviours (Kuo, 2006;Kim et al, 2010; nomenclature follows Alexander et al, 2013). Dopamine may decrease NPY but increase POMC in the hypothalamus, resulting in decreased food intake in amphetamine-treated rats (Chen et al, 2001;Kuo et al, 2011;2012a). Hypothalamic NPY is a highly conserved neuropeptide that regulates feeding behaviour, energy balance (Mercer et al, 2011) and stress response (Morales-Medina et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…PKC-λ is a Ca 2+ independent, but triacylglycerol dependent, atypical PKC isoform. Kuo et al, (2011) showed that PKC-λ mediated the appetite-suppressing effect of PPA by increasing oxidative stress. The increased ROS production stimulated POMC activity and inhibited NPY activity [42].…”
Section: Hypothalamic Ros Regulates Glucose and Fatty Acid Sensingmentioning
confidence: 99%
“…However, the capacity for production of ROS by the NPY/AgRP is reported to be low. 15 The generation of hypothalamic ROS is not only driven by nutrient sensing alone, it is also regulated by hormones like ghrelin, leptin and insulin. Ghrelin is a gut derived hormone that activates NPY/AgRP neurons and increases food intake by modulating ROS levels.…”
Section: Effect Of Nutrients and Hormones On Hypothalamic Ros Productionmentioning
confidence: 99%
“…12 NPY/AgRP neurons on the other hand do not produce considerable quantity of ROS, as these neurons appear to have low ROS production capacity and a high ROS buffering capacity. 10,15 Another factor controlling ROS production in hypothalamic neurons is calcium (Ca 30 which in turn stimulates AMPK pathways, generates ATP, facilitates fatty acid oxidation and results in increased ROS production. 31,32 Increase intracellular Ca 2+ concentration leads to increase mROS generation which also elevates the cellular oxidative stress.…”
Section: Factors Influencing Generation Of Hypothalamic Rosmentioning
confidence: 99%